Implementation of the Principle of Due Process of Law in Handling General Crimes in Indonesia - Heriyanto Manurung; Rahmayanti; Muhammad Arif Sahlepi (CV. Era Digital Nusantara, 2026)
The principle of due process of law is one of the principles of a state based on the rule of law that guarantees the protection of human rights, particularly for suspects or defendants in criminal justice processes. In Indonesia, this principle is enshrined in various legal instruments, including the 1945 Constitution, the Criminal Procedure Code (KUHAP), and a number of implementing regulations that emphasize the importance of fair, transparent, and non-arbitrary treatment during the investigation, prosecution, and trial processes. However, the implementation of this principle in handling general crimes still faces various problems, such as abuse of authority by law enforcement officers, criminalization practices, and disparities in the treatment of perpetrators. This study uses a normative juridical approach by analyzing regulations, doctrine, and judicial practices. The results show that although the principle of due process of law has been integrated into the Indonesian legal system, its implementation is not fully consistent. Constraints include weak oversight, lack of understanding among officials, and social and political pressures in case handling. Therefore, strengthening internal and external oversight mechanisms, increasing the capacity of law enforcement officers, and updating regulations with a greater emphasis on procedural standards are necessary. Thus, the application of the principle of due process of law in general crimes can be optimally implemented to achieve legal certainty, justice, and the protection of human rights.